Translation Shift of ‘Jakarta Post’ newspaper on Monday, November 17, 2014 page 5, the first column with the title “UNHAS deputy rector named as suspected drug user” - Fernando De Napoli Marpaung; Yusrah (LPPM STKIP AL MAKSUM, 2021)
Translation shifts is a changing of form when it is translated from the source language into target language. In this study writer focus in translation shift and the most dominant of shift in the process of translating a discourse in “Jakarta Post” newspaper. This study conducts on the descriptive qualitative method. Descriptive design simply describes what data shows. In order to account for this, the writer use a wide variety of translation shift in order to accurately translate any given text. Based on the data analysis which is taken from ‘Jakarta Post’ newspaper on Monday, November 17, 2014 page 5, first column with the title “Unhas deputy rector named as suspected drug user”. The Jakarta Post is a daily English-language newspaper in Indonesia. The paper is owned by PT Niskala Media Tenggara and based in the nation's capital, Jakarta. The writer use theories of Catford, there are any major types of translation shifts. They are structure shift, unit shift, class shift and intra – system shift. In 20 sentences (including the title) the writer use 13 times to structure shift (44.9%), 9 times to unit shift (31.1%), 1 time to class shift (3.4%) and 6 times to intra – system shift (20.6%). So, Structure shift is the most dominant that be used by writer to translate the data.